Dose–volume constraints for head‐and‐neck cancer in carbon ion radiotherapy: A literature review. (17th February 2023) - Varnava, Maria; Musha, Atsushi; Tashiro, Mutsumi; Kubo, Nobuteru; Okano, Naoko; Kawamura, Hidemasa; Ohno, Tatsuya
Abstract: Background: Carbon ion radiotherapy (CIRT) has been applied in cancer treatment for over 25 years. However, guidelines for dose–volume constraints have not been established yet. The aim of this review is to summarize the dose–volume constraints in CIRT for head‐and‐neck (HN) cancer that were determined through previous clinical studies based on the Japanese models for relative biological effectiveness (RBE). Methods: A literature review was conducted to identify all constraints determined for HN cancer CIRT that are based on the Japanese RBE models. Results: Dose–volume constraints are reported for 17 organs at risk (OARs), including the brainstem, ocular structures, masticatory muscles, and skin. Various treatment planning strategies are also presented for reducing the dose delivered to OARs. Conclusions: The reported constraints will provide assistance during treatment planning to ensure that radiation to OARs is minimized, and thus adverse effects are reduced. Although the constraints are given based on the Japanese RBE models, applying the necessary conversion factors will potentially enable their application by institutions worldwide that use the local effect model for RBE. Abstract : This study summarizes the dose–volume constraints for head and neck cancer in carbon ion radiotherapy that are based on the Japanese models for relative biological effectiveness. The constraints are divided into hard and soft to help in deciding which constraints to prioritize during plan optimization. Applying the necessary conversion factors will potentially enable their application by institutions that use the local effect model.